Taxonomic review of the Neotropical genus Moriosomus Motschulsky (Insecta: Coleoptera, Carabidae, Morionini) with notes on the way of life of the species - Erwin, Terry L.; Moore, Wendy (Zootaxa, 2007)
Moriosomus Motschulsky 1855 is a Neotropical genus containing three species in the carabid beetle tribe Morionini. Moriosomus adults are found under tree bark and in rotting logs in rainforests; larvae are unknown. This revision of Moriosomus includes diagnoses, descriptions, illustrations, and distributional data for all three known species, including Moriosomus motschulskyi Erwin & Moore, new species (“PERU, HUáN[UCO], Divisoria,” Cordillera Azul, 1600m, 08° 54’ 0 S, 075° 40’ 0 W). We provide an identification key to the species based on adult external structure. We clarify the the date of the description of the genus Moriosomus, which is 1855, rather than 1864 as it is often incorrectly cited in the literature. In addition, we define the tribe Morionini and provide a key for identification of the two genera resident in the Western Hemisphere.